2022
DOI: 10.1002/nau.24888
|View full text |Cite
|
Sign up to set email alerts
|

Urinary incontinence, overactive bladder, and quality of life in women submitted to total hip replacement

Abstract: Introduction and Hypothesis Hip osteoarthritis (OA) compromises functioning. Total hip replacement (THR) is the indicated treatment and may improve urinary incontinence (UI) and symptoms of overactive bladder (OAB). Objectives Assess UI, OAB symptoms, and quality of life (QoL) impact in preoperative and postoperative periods of women submitted to THR and investigate associated factors. Methods A prospective cohort was conducted with 183 women submitted to THR. The International Consultation on Incontinence Que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In both cases, improving mobility may be more beneficial than focusing specifically on the pelvic floor or detrusor muscle. A prospective study, with a cohort of 183 women submitted to total hip replacement due to hip OA, observed significant improvements in UI and mobility, assessed by the physical component of SF‐12, 3,‐ and 6‐month postoperatively 25 . However, higher levels of evidence are necessary, including older women with knee OA.…”
Section: Discussionmentioning
confidence: 99%
“…In both cases, improving mobility may be more beneficial than focusing specifically on the pelvic floor or detrusor muscle. A prospective study, with a cohort of 183 women submitted to total hip replacement due to hip OA, observed significant improvements in UI and mobility, assessed by the physical component of SF‐12, 3,‐ and 6‐month postoperatively 25 . However, higher levels of evidence are necessary, including older women with knee OA.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of randomized controlled trials on rehabilitation have reported that hip rehabilitation contributed to the strengthening of the pelvic floor muscles and the improvement of stress urinary incontinence (Jordre & Schweinle, 2014; Tuttle et al, 2016). Several studies, including a prospective cohort, reported that improved hip function with total hip arthroplasty improved urinary incontinence (Baba et al, 2014; Martines et al, 2022; Okumura et al, 2017; Tamaki et al, 2014). An electromyography study reported that electrophysiological stimulation of the fascia of the obturator internus resulted in the contraction of the levator ani (Chin et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that balanced and proper movements of the obturator internus contribute to the function of the LA, that is, pelvic floor support. Various aspects of the functional relationship between the LA and obturator internus have been suggested, including reports that hip rehabilitation contributed to the strengthening of the pelvic floor muscles and the improvement of stress urinary incontinence (Jordre and Schweinle 2014 ; Tuttle et al 2016 ), reports that hip function with total hip arthroplasty improved urinary incontinence (Baba et al 2014 ; Martines et al 2022 ; Okumura et al 2017 ; Tamaki et al 2014 ), and a report that electrophysiological stimulation of the fascia of the obturator internus resulted in LA contraction (Chin et al 2021 ).…”
Section: Skeletal Muscles Of Pelvic Outletmentioning
confidence: 99%